HUBUNGAN SELF AWARENESS DENGAN QUARTER LIFE CRISIS PADA SISWA MAN 1 LANGSA - Dinda Elvadiana; Mawardi Siregar; Wan Chalidaziah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Quarter life crisis is a period of transition from late adolescence to early adulthood, namely between the ages of 18-30 years. This condition occurs because of a person's inability and indecision in facing an uncertain future. To avoid a quarter life crisis, self awareness is required. This study focuses on examining the description of self awareness and quarter life crisis of MAN 1 Langsa students. This study also reviews the relationship between self awareness and quarter life crisis. The research method used is quantitative correlation. This study reveals that the self awareness of MAN 1 Langsa students is high, namely 52.4% and the quarter life crisis is moderate, namely 46.8%. This study also reveals that there is a relationship between self awareness and quarter life crisis with a sig value of 0.006. The correlation coefficient is -0.263 or 26.3%. The higher the self awareness the lower the quarter life crisis. Conversely, the lower the self awareness, the higher the quarter life crisis. Thus, this study strengthens the argument that self awareness plays an important role in overcoming the occurrence of a quarter life crisis.